Valproic Acid Induces Autism-Like Synaptic and Behavioral Deficits by Disrupting Histone Acetylation of Prefrontal Cortex ALDH1A1 in Rats - Liu, Huan; Tan, Mei; Cheng, Boli; Wang, Si; Xiao, Lu; Zhu, Jiang; Wu, Qionghui; Lai, Xi; Zhang, Qian; Chen, Jie; Li, Tingyu (Frontiers in Neuroscience, 2021)
Objectives: This study aimed to investigate the impact of valproic acid (VPA) on the histone acetylation of acetaldehyde dehydrogenase 1A1 (ALDH1A1) and the mechanism underlying VPA-induced autism-like behavior. Methods: Female Sprague-Dawley rats were intraperitoneally injected with VPA during gestation to establish an autism model in their offspring. Some offspring prenatally exposed to VPA were randomly treated with MS-275, one histone deacetylase (HDAC) inhibitor, or retinoic acid (RA) after birth. Behavioral tests were conducted on the offspring six weeks after birth. Electrophysiological experiments were performed to investigate long-term potentiation (LTP) in the prefrontal cortex (PFC). The expression levels of AMPA receptors (GluA1 and 2), NMDA receptors (GluN1 and 2), synapsin 1 (SYN1), HDAC, acetylated histone 3 (AcH3), RA receptor alpha (RARα), and ALDH1A1 in the PFC were measured by Western blotting and qPCR. ALDH enzyme activity in PFC tissue was detected using a Micro ALDH Assay Kit. The RA level in the PFC was measured using UPLC-MS/MS. A ChIP experiment explored the interaction between the ALDH1A1 gene and AcH3. Results: Offspring prenatally exposed to VPA showed autism-like behavior, upregulated the levels of LTP and GluN2A, GluA1 and SYN1 proteins relevant to synaptic plasticity in the PFC. The expression levels of HDAC3 mRNA and protein were increased. On the other hand, there was a significant reduction in the levels of AcH3, RARα, RA, ALDH1A1 mRNA and protein, the level of ALDH activity and AcH3 enrichment in the ALDH1A1 promoter region in VPA-induced offspring. Administration of MS-275 in VPA offspring significantly elevated the levels of AcH3, ALDH1A1 mRNA and protein, ALDH activity, RA, the level of RARα protein and the binding of AcH3 to the ALDH1A1 promoter. In addition, the GluA1 protein level and LTP were reduced, and most behavioral deficits were reversed. After RA supplementation in the VPA-treated offspring, the RA and RARα protein levels were significantly upregulated, GluA1 protein and LTP were downregulated, and most autism-like behavioral deficits were effectively reversed. Conclusions: These findings suggest that VPA impairs histone acetylation of ALDH1A1 and downregulates the RA-RARα pathway. Such epigenetic modification of ALDH1A1 by VPA leads to autism-like synaptic and behavioral deficits.